Development and experimental analysis of a small integrated edge navigation sensor based on principle of circular arc array - Xie, Binbin; Liu, Jizhan; Jiang, Houkang; Cai, Lianjiang; Liu, Lu; Li, Yuanxiang (Frontiers in Plant Science, 2022)
Due to the existing autonomous navigation technologies such as satellite, radar and machine vision have the problems of weak signal, poor accuracy and insufficient real-time performance, and there is no navigation sensor for special facility agricultural environment on the market. In order to solve this problem, in this study, according to a position and orientation detection method based on the ideal target band principle of a central photoelectric arc array, a position and orientation state determination rule and a pose deviation calculation formula for the unknown number of photoelectric switches are established, the miniaturization scheme of zooming detection arc based on variable central angle is proposed, the adjustment equation of the detection distance of photoelectric switches at each position is established, and a small integrated photoelectric arc array navigation sensor with a cost of about $65 is developed using an embedded microcontroller.